Intramolecular construction of trifluoromethyl group by the palladium-catalyzed reaction of 2, 3, 3-trifluoroallylic carbonates with O-nucleophiles. Issue 13 (29th March 2018) - Hoshino, Yuji; Isa, Kazuki; Hanakawa, Taisyun; Tsuji, Hiroaki; Kawatsura, Motoi
Abstract: The synthesis of the trifluoromethyl group containing enol ethers by the palladium-catalyzed intermolecular reaction of 2, 3, 3-trifluoroallylic carbonates with oxygen nucleophiles was accomplished. The reaction proceeds through the intermolecular attack of oxygen nucleophiles on the C-2 carbon atom of the allylic unit, and the intramolecular fluorine atom shift from the C-2 position to the C-3 position. The reactions with several types of alcohols and phenols proceeded smoothly, and afforded the corresponding trifluoromethyl group containing enol ethers in good to high yields. Graphical abstract: